Big book to increase 5th grade students’ reading literacy - Dian Permatasari Kusuma Dayu; Niken Dwi Setyaningsih (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2022)
This study aims to determine the effect of using big book media on students' reading literacy in class. This research used a quantitative approach. The research design was a pre-experimental one-group pretest-posttest design. Data collection techniques using tests and observations. The data analysis techniques were validity, reliability, normality, homogeneity, t-test, and N-gain tests. The subjects of this study were 50 students of grade V consisting of 35 females and 15 males. The results show that there is a significant effect of big book media on the reading literacy of grade V students in elementary schools. The results of the Statistical analysis of the t-count test is 6.349 t-table 2,0. It can be concluded that big book media, is effective on students reading literacy.